Aberrant p27Kip1 promoter methylation in malignant melanoma - Worm, J; Bártková, Jiřina; Kirkin, A.F; Straten, P; Zeuthen ,J; Bártek, Jiří; Guldberg, P (Oncogene, 2000)
p27Kip1 is a regulator of the mammalian cell cycle and a putative tumor suppressor. Distinct altered patterns of p27Kip1 protein expression are found in a variety of human carcinomas, and p27Kip1 expression levels usually correlate directly with disease-free survival. The mechanism(s) by which p27Kip1 expression is reduced or lost during tumorigenesis remains unclear. Specific alterations of the p27Kip1 gene, including mutations and homozygous deletions, are exceedingly rare in human cancers. We have used methylation-specific PCR and bisulfite genomic sequencing to examine the methylation status of p27Kip1 in 61 primary and metastatic tumors and 35 cell lines from patients with malignant melanoma. Dense methylation of a CpG island in the promoter region of p27Kip1 was detected in four of 45 metastatic tumors (9%) and three of the cell lines (9%), including two cell lines established from two different metastases from the same patient. Examination of a naturally occurring, allele-specific sequence variant demonstrated that p27Kip1 methylation is associated with transcriptional silencing in situ. Cell lines with p27Kip1 methylation showed retention of the wild-type allele and detectable p27Kip1 protein whose abundance was reduced compared with normal melanocytes. Collectively, our data suggest that DNA methylation may be a cause of monoallelic p27Kip1 silencing in malignant melanoma, which would support a role for p27Kip1 haploinsufficiency in human cancer.
Keywords: Promoter Regions, Genetic; proteiny buněčného cyklu; Gene Expression Regulation, Neoplastic; Cell Cycle Proteins; lidé; Melanoma; Humans; Mutation; promotorové oblasti (genetika); nádorové supresorové proteiny; Microtubule-Associated Proteins; Tumor Suppressor Proteins; substituce aminokyselin; aktivace transkripce; Transcriptional Activation; metylace DNA; Cyclin-Dependent Kinase Inhibitor p27; melanom; CpG ostrůvky; polymerázová řetězová reakce; proteiny asociované s mikrotubuly; Polymerase Chain Reaction; DNA Methylation; umlčování genů; Amino Acid Substitution; messenger RNA; inhibitor p27 cyklin-dependentní kinasy; mutace; Gene Silencing; regulace genové exprese u nádorů; melanocyty; Melanocytes; CpG Islands; RNA, Messenger